2002
DOI: 10.1046/j.0007-1323.2001.01974.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of suture repair, polypropylene mesh or autodermal hernioplasty for incisional hernia

Abstract: Suture repair was safe for small incisional hernias. Both autoplastic and alloplastic hernia repair yielded comparably low recurrence rates, but led to a high rate of wound infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
1
13

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(193 citation statements)
references
References 19 publications
6
173
1
13
Order By: Relevance
“…6,17 Large trials have shown that hernia repair should be performed by mesh placement and no longer by primary resuturing of the hernia because of unacceptably high recurrence rates. 7,19 Mesh repair, however, is not free from complications, with significant factors being technical failure such as insufficient fixation of the mesh to the abdominal wall and complications which are a result of the mesh biomaterial itself. The latter is especially true if the biomaterial provokes inflammation, or if its surface is prone to bacterial infection.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…6,17 Large trials have shown that hernia repair should be performed by mesh placement and no longer by primary resuturing of the hernia because of unacceptably high recurrence rates. 7,19 Mesh repair, however, is not free from complications, with significant factors being technical failure such as insufficient fixation of the mesh to the abdominal wall and complications which are a result of the mesh biomaterial itself. The latter is especially true if the biomaterial provokes inflammation, or if its surface is prone to bacterial infection.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Scores on the measure were also able to differentiate groups of gastrointestinal patients with different levels of function, as well as between those with gastrointestinal disease and those who were ostensibly normal. Responsiveness is obviously highest in gastroesophageal disorders, but the GIQLI has also been used with variable responsiveness in other abdominal operations [14,19,42,65,73]. The GIQLI is available on the Quality of Life Database developed by the nonprofit Mapi Research Institute.…”
Section: Gastrointestinal Quality Of Life Index (Giqli)mentioning
confidence: 99%
“…In the literature, several studies have assessed the body's reaction to polypropylene mesh implantation, which is widely used for the repair of abdominal wall defects of different etiologies. However, most studies seek to assess the rates of recurrence, infection and inflammatory response, and the presence of adhesions associated with the use of different mesh types available in the market [7][8][9] . According to the literature, since polypropylene mesh acts as a foreign body in the surgical wound, it could cause a prolonged inflammatory response (chronic inflammatory reaction) retarding progression to the proliferative phase of healing, which is responsible for the tensile strength of the scar 8,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are several synthetic materials available, but polypropylene mesh is definitely the most widely used, with the most recorded experience 6,7 . The main characteristic of these meshes are that they are inert when infection occurs, that they maintain the tensile strength of the abdominal wall and have an excellent capacity for integration 2 , besides being low cost and malleable, and they have already been tested for years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation